Предмет: Алгебра,
автор: filippka1406
Какое из выражений эквивалентно выражению 2(3b - 1) + 4
6b + 6
6b - 2
6b + 2
3b + 7
3b - 4
Ответы
Автор ответа:
1
Ответ:
Выпржение эквивалентно выражению 2(3b-1)+4 это 6b+2
Объяснение:
2(3b-1)+4=6b-2+4=6b+2
Автор ответа:
1
Объяснение:
2(3в - 1) + 4 = 2*3в - 2*1 + 4 = 6в - 2 + 4 = 6в + 2
Похожие вопросы
Предмет: Математика,
автор: Tsagaantuya
Предмет: Физика,
автор: pilipecila59
Предмет: Українська мова,
автор: s1rex0211
Предмет: Информатика,
автор: nicom17
Предмет: Геометрия,
автор: ukreune24